Efficacy and safety of dapagliflozin in children and young adults with type 2 diabetes: a prospective, multicentre, randomised, parallel group, phase 3 study. Issue 5 (May 2022) - Tamborlane, William V; Laffel, Lori M; Shehadeh, Naim; Isganaitis, Elvira; Van Name, Michelle; Ratnayake, Jayantha; Karlsson, Cecilia; Norjavaara, Ensio
Summary: Background: Since there are few treatment options for young people with type 2 diabetes, we aimed to assess the efficacy and safety of dapagliflozin as add-on therapy in children, adolescents, and young adults with type 2 diabetes receiving metformin, insulin, or both. Methods: This multicentre, placebo-controlled, double-blind, randomised phase 3 study was undertaken at 30 centres in five countries (Hungary, Israel, Mexico, Russia, and the USA). Participants aged 10–24 years with type 2 diabetes and HbA1c concentration of 6·5–11% (48–97 mmol/mol) were randomly assigned 1:1 to oral dapagliflozin 10 mg or placebo during a 24 week double-blind period, which was then followed by a 28 week open-label safety extension in which all participants received dapagliflozin. Participants and study personnel were masked and participants were randomly assigned treatment (placebo or study drug) using an interactive web and voice response system. The primary outcome was between-group differences in change in HbA1c concentration from baseline to 24 weeks (intention-to-treat analysis). A prespecified sensitivity analysis of the primary outcome was also assessed in the per-protocol population, which included only protocol-compliant participants. This trial is registered with ClinicalTrials.gov, NCT02725593 . Findings: Between June 22, 2016, and March 15, 2019, 72 participants (19 [26%] of whom were aged 18–24 years) were randomly assigned (39 to dapagliflozin and 33 to placebo). Mean age was 16·1 (SD 3·3) years. In the intention-to-treat analysis, after 24 weeks, mean change in HbA1c concentration was −0·25% (95% CI −0·85 to 0·34; −2·7 [−9·3 to 3·7] mmol/mol) for dapagliflozin and 0·50% (−0·18 to 1·17; 5·5 [−2·0 to 12·8] mmol/mol) for placebo. The between-group difference was −0·75% (95% CI −1·65 to 0·15; −8·2 [−18·0 to 1·6] mmol/mol; p=0·10). In a sensitivity analysis in the per-protocol population (34 in the dapagliflozin group and 26 in the placebo group) after 24 weeks, mean change was −0·51% (−1·07 to 0·05; −5·6 [−11·7 to 0·5] mmol/mol) for dapagliflozin and 0·62% (−0·04 to 1·27; 6·8 [−0·4 to 13·9] mmol/mol) for placebo. The between-group difference was −1·13% (−1·99 to −0·26; −12·4 [−21·8 to −2·8] mmol/mol; p=0·012). Adverse events occurred in 27 (69%) dapagliflozin-assigned participants and 19 (58%) placebo-assigned participants over 24 weeks, and in 29 (74%) participants who received dapagliflozin over 52 weeks. Hypoglycaemia occurred in 11 (28%) dapagliflozin-assigned and six (18%) placebo-assigned participants who received dapagliflozin over 24 weeks and in 13 participants (33%) who received dapagliflozin over 52 weeks; none were considered as serious adverse events. No adverse events of diabetic ketoacidosis occurred. Interpretation: The primary outcome of change in HbA1c concentration was not significant in the intention-to-treat analysis of children, adolescents, and young adults with type 2 diabetes receiving dapagliflozin in addition to standard-of-care treatment. A prespecified sensitivity analysis of protocol-compliant participants showed a significant difference in HbA1c concentration between groups. No new safety signals were identified and there was a low risk of severe hypoglycaemia. Funding: AstraZeneca.